1997
DOI: 10.1111/j.1365-2567.1997.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immune dysfunction during murine leukaemia retrovirus infection of old mice by dehyroepiandrosterone sulphate (DHEAS)

Abstract: SUMMARYAgeing, leukaemia and acquired immune deficiency syndrome (AIDS ) are conditions with dysregulated cytokine production. As dehydroepiandrosterone sulphate (DHEAS ) restored normal cytokine production in old mice its effects on retrovirally infected old mice were investigated. Retrovirus infection and ageing-induced immune dysfunction. Murine retrovirus-infected old C57BL/6 female mice consumed 0·22 or 0·44 mg of DHEAS/mouse/day beginning 2 weeks postinfection for 10 weeks. DHEAS largely prevented the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
3
26
1
2
Order By: Relevance
“…In this study, both aged and young animals immunized with mycHSP70 and DHEAS presented significantly higher levels of IFN-c. This corroborates previous data showing increased IFN-c levels in retrovirus-infected aged C57/BL6 mice that received DHEAS orally (Araghi-Niknam et al 1997). It has been shown that immunization to proteins in IFA or alum as adjuvants induced polarized Th2 immune responses in neonatal and young adult mice, characterized by the production of antigenspecific IL-4, IL-5, IgG1 and IgE, but not IFN-c or IgG2a (Chu et al 1997;Yip et al 1999).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, both aged and young animals immunized with mycHSP70 and DHEAS presented significantly higher levels of IFN-c. This corroborates previous data showing increased IFN-c levels in retrovirus-infected aged C57/BL6 mice that received DHEAS orally (Araghi-Niknam et al 1997). It has been shown that immunization to proteins in IFA or alum as adjuvants induced polarized Th2 immune responses in neonatal and young adult mice, characterized by the production of antigenspecific IL-4, IL-5, IgG1 and IgE, but not IFN-c or IgG2a (Chu et al 1997;Yip et al 1999).…”
Section: Discussionsupporting
confidence: 83%
“…It also decreases the spontaneous secretion of IL 6 (576) and IL 10 observed in old mice and reverses their hypersensitivity to endotoxin-stimulated release of both IL 6 and IL 10 (577), and enhances lymphocyte activation (578). Analogously, it prevents the retrovirus-induced increased IL 6 and IL 10 secretion seen in old mice, prevents decreases of IL 2 and IFN-gamma production and enhances their T and B cell proliferative responses (579). IL 6 may be the critical cytokine here, because treating aged mice with IL 6-but not IL 1-neutralizing antibody resulted in a reversion of their cytokine production pattern to that characteristic of young animals (580).…”
Section: Hormonesmentioning
confidence: 84%
“…(12,13) The 5-androstene steroids provide resistance to infection by stimulating immune responses. (14)(15)(16)(17) Based on the fact that these steroids enhance resistance to infection after administration in animals, (14)(15)(16)(17) we evaluated these steroids for their radioprotective efficacy in the mouse model against cobalt-60 gamma irradiation. We observed that single injections of 5-AED 24 to 48 hr before or 2 hr after whole body gamma irradiation significantly enhanced survival, increased granulocytemonocyte progenitors in bone marrow, and elevated numbers of granulocytes, monocytes, natural killer cells, platelets, and erythrocytes in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%